Lateral impact performances of geopolymer concrete columns reinforced with steel-BFRP composite bars - Huang, Zhijie; Chen, Wensu; Hao, Hong; Siew, Audrey Ung; Huang, Tairu; Ahmed, Mizan; Pham, Thong (Elsevier, 2024)
There is a growing public interest in exploring materials that can enhance the sustainability and durability of conventional steel reinforced concrete (RC) structures, such as geopolymer concrete (GPC) and steel-fibre reinforced polymer composite bars (SFCBs). GPC is produced with industrial waste such as fly ash and slag to replace ordinary Portland cement concrete (OPC), and SFCB is a new reinforcement bar with a layer of fibre reinforced polymer (FRP) enclosing a steel inner core to protect it from corrosion. No studies have ever been reported on the impact-resistant performances of GPC or fibre-reinforced GPC (FRGPC) columns reinforced with SFCBs subjected to vehicle or ship impacts. In this study, GPC/FRGPC columns reinforced with steel-basalt FRP composite bars (SBCBs) were prepared and tested by a pendulum impact testing system. Their impact-resistant performances were compared. It was found that the columns experienced similar damage modes regardless of reinforcement type and fibre content. The addition of hybrid carbon fibres (CFs) and basalt macro fibres (BMFs) could effectively reduce cracking damage and mid height deflections of columns. As compared to steel bar reinforcements, SBCB reinforcements led to similar impact force and maximum mid height deflections, but could reduce the residual mid height deflections of the columns by 7–42% under the impact velocity of 2.64–3.49 m/s, indicating SBCBs have great potential to replace steel bars in constructing more sustainable and durable concrete structures.